Dust grains potential variation in a Vasyliunas Cairns-distributed plasmas with negative ions - Abid, A.A.; Khan, M.Z.; Wong, C.S.; Yap, S.L. (2015)
Dust grains' potential variation is presented by using a non-equilibrium complex (dusty) plasma following the Vasyliunas Cairns (VC)-distribution, in which the components such as the electrons, ions [positive and negative], and dust grains have negative charge. For this reason, mathematical statement of currents is solved for dust grains having negatively charge to accomplish the equilibrium state value (viz., q(d) = constant) in the presence of VC-distributed plasmas. Indeed, the current balance equations are modified due to the streaming/nonequilibrium distributed negative ions. Numerically, it is assessed that the important plasma variable, for example, spectral index alpha, spectral index kappa; negative ions streaming velocity (U-0), and negative ions number density (rho), significantly influences the dust grain surface potential (vertical bar psi(d)vertical bar) by: (i) increasing the value of spectral index kappa (kappa) and negative ions density (rho), the magnitude of dust surface potential (vertical bar psi(d)vertical bar) decreases and (ii) increasing the values of spectral index alpha and negative ions streaming velocity (U-0), dust grains surface potential (vertical bar psi(d)vertical bar) increases. The relevance to low-temperature research center in a non-equilibrium dusty (complex) plasma is precisely discussed by associating oxygen ions (negative and positive) species. (c) 2015 AIP Publishing LLC.